HUBUNGAN ANTARA TINGKAT PENDIDIKAN DENGAN SIKAP DAN PERILAKU IBU RUMAH TANGGA DALAM PEMELIHARAAN KEBERSIHAN LINGKUNGAN TEMPAT TINGGAL DI DESA KLALING KECAMATAN JEKULO KABUPATEN KUDUS - Fatih, Failasufa Dhiyaul (Universitas Negeri Semarang, 2015)
In this study, there are two types of environments under study , the natural environment and social environment.The purpose of this study was determine the level of education in the village housewife Klaling Jekulo District ofKudus Regency, the behavior of the housewife in the maintenance of environmental hygiene in the village Klaling,determine the relationship between the mother's level of education and household behavior in the maintenance ofenvironmental hygiene with a total population 2,539 people. The sampling technique using Random Sampling.The attitude of the housewife in the maintenance of cleanliness of the neighborhood turned out to be none noattitude with the criteria strongly disagree. And to conduct housewives already know and understand how theactions and behaviors in maintaining the cleanliness of the neighborhood. The results showed levels of educationhousewives are a number of educational level of 9.28 % Housewife (elementary school), then 22.68 % Housewifewith high enough criteria, 58.76 % Housewife with high criteria, and 9.28 % Housewife with very high criteria (college ). It can be concluded that the housewife can determine or make a change in the maintenance ofcleanliness of the neighborhood. Government needs more hygiene promotion for the sake of understanding of thehome environment quality homes.